Theatrical convention and audience response in early modern drama - Lopez, Jeremy (Cambridge University Press, 2003)
In this comprehensive survey of the diverse, theatrically vital formal conventions of the drama of Shakespeare and his contemporaries, Lopez proposes that understanding the potential for theatrical failure - the way playwrights anticipated it and audiences responded to it - is crucial for understanding how the drama succeeded on the stage.